A Collaborative Governance Model to Prevent and Reduce Early Muslim Divorce through Islamic Economic Empowerment and Family Financial Resilience in the Horseshoe Region: A Maqashid al-Shari'ah Perspective - Muzayyanah; Iffatin Nur; Dede Nurrahman (LAN TABUR: Jurnal Ekonomi Syariah The Islamic University of KH. Achmad Muzakki Syah Jember, East Java. Jember Jln. Manggar Gebang Poreng 139A Patrang Jember Jawa Timur, 2026)
Purpose – This study aims to formulate a collaborative governance model for the prevention and mitigation of early divorce among Muslim families in the Tapal Kuda region of East Java through the perspective of Maqashid al-Syari’ah as developed by Jamaluddin Athiyyah. The increasing rate of marital instability and early divorce has become a critical social issue that threatens family resilience and the achievement of Islamic family welfare. This study argues that collaborative governance involving multiple stakeholders can strengthen family resilience and reduce divorce risks through an integrated and value-based approach. Design/methods/approach – This research employs a qualitative approach with a case study design. Data were collected through in-depth interviews, observations, and document analysis involving religious affairs offices, religious courts, local governments, Islamic organizations, community leaders, marriage counselors, and affected families in the Tapal Kuda region. Data were analyzed using an interactive model consisting of data reduction, data display, and conclusion drawing, while the analytical framework was based on collaborative governance theory and Jamaluddin Athiyyah’s Maqashid al-Syari’ah. Findings – The study reveals that effective divorce prevention requires collaborative engagement among governmental, religious, and community institutions. The collaborative model contributes to strengthening five dimensions of family resilience: religious, educational, economic, social, and psychological resilience. The implementation of premarital education, family counseling, economic empowerment, and community-based mediation significantly enhances family stability and aligns with the maqashid objectives of preserving religion (hifz al-din), family lineage (hifz al-nasl), intellect (hifz al-‘aql), wealth (hifz al-mal), and human dignity (hifz al-karamah). Research implications/limitations – The findings are limited to the socio-cultural context of the Tapal Kuda region and may not be fully generalizable to other regions with different demographic characteristics. Originality/value – This study offers a novel integration of collaborative governance and Jamaluddin Athiyyah’s Maqashid al-Syari’ah framework as a comprehensive strategy for strengthening Muslim family resilience and addressing early divorce through multi-stakeholder cooperation.